ChemInform Abstract: Chemoselective Claisen—Schmidt Bis‐substitutional Condensation Catalyzed by an Alkoxy‐Bridged Dinuclear Ti(IV) Cluster. Issue 28 (June 2016) - Wu, Yufei; Hou, Jie; Liu, Yuliang; Zhang, Mingfu; Tung, Chen‐Ho; Wang, Yifeng
Abstract: An efficient approach to a series of α, α‐bis‐substituted alkanone structures becomes possible in the presence of DTC (mechanism of the catalytic process).